2020
DOI: 10.3390/aerospace7100150
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Control Allocation Method for Yaw Control of Tailless Aircraft

Abstract: Tailless aircraft without vertical stabilisers typically use drag effectors in the form of spoilers or split flaps to generate control moments in yaw. This paper introduces a novel control allocation method by which full three-axis control authority can be achieved by the use of conventional lift effectors only, which reduces system complexity and control deflection required to achieve a given yawing moment. The proposed method is based on synthesis of control allocation modes that generate asymmetric profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The results of the simulation showed that the adverse yaw effect was reduced by 25%. Further reduction of the effect can be obtained using optimization rules (Shearwood et al, 2020). Figure 7(a) shows aerodynamic efficiency vs angles of attack of the aircraft for a few chosen spoiler configurations.…”
Section: Elevons Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the simulation showed that the adverse yaw effect was reduced by 25%. Further reduction of the effect can be obtained using optimization rules (Shearwood et al, 2020). Figure 7(a) shows aerodynamic efficiency vs angles of attack of the aircraft for a few chosen spoiler configurations.…”
Section: Elevons Designmentioning
confidence: 99%
“…The results of the simulation showed that the adverse yaw effect was reduced by 25%. Further reduction of the effect can be obtained using optimization rules (Shearwood et al , 2020).…”
Section: Control Surfaces Designmentioning
confidence: 99%
See 1 more Smart Citation
“…They range from large-scale drones, similar to the Global Hawk, through miniature systems (e.g., [39][40][41]), to the latest nano and pico air vehicles (e.g., [42][43][44][45]). These platforms have enabled testing of innovative aerial solutions, e.g., control strategies [46][47][48][49], difficult to apply in manned aircraft. Drones are categorized into several types based on mission capabilities, including horizontal take-off and landing (HTOL), vertical take-off and landing (VTOL), various hybrids, helicopters, and unconventional designs [50].…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…Whilst there are existing approaches for automated storage mapping such as using laser scanners [1], there is still an essential need for low-cost, low-intervention, and highly versatile solutions for such high-hazard industries. Unmanned aerial vehicles (UAVs), commonly known as drones, are developed with different configurations and have been deployed to tackle challenges in wide range of applications [2][3][4][5][6][7][8]. Recent years have witnessed increased use of drones within a variety of civil applications such as monitoring of difficult-to-access infrastructures, spraying fields and performing surveillance in precision agriculture, delivering packages and safety inspection.…”
Section: Introductionmentioning
confidence: 99%